Communication : principles for a lifetime - Beebe, Steven A.; Beebe, Susan J.; Ivy Diana K. (Boston : Allyn & Bacon, 2010)
Communication helps readers see the relationships among the concepts, skills, theories, and contexts of communication by anchoring all discussion around five fundamental principles. Written by experienced and highly regarded textbook authors and teachers, Communication:Principles for a Lifetime provides readers with all the theory and skills necessary in the introductory course - in a manner that will help them to apply what they learn throughout their lives. Understanding that the challenge of basic communication is learning the myriad of skills, principles, and theories, Beebe/Beebe/Ivy emphasize five key principles of communication throughout their book: Be aware of your communication with yourself and others. Effectively use and understand verbal messages. Effectively use and understand nonverbal messages. Listen and respond thoughtfully to others. Appropriately adapt messages to others. For anyone interested in the art of communication.
Includes reference and index
Keywords: Communication